Management Plan for Gili Tangkong, Gili Nanggu and Gili Sudak Marine Conservation Area (MCA) West Lombok District - Husni, Syarif; Yuniarti, Salnida; Junaidi, Muhammad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Ecologically, conservation areas play an important role in protecting the sustainability of ecosystems, where natural resources are able to maintain their reciprocal relationship and interdependence between marine biota and their physical environment. The purpose of this study is to describe the planning in the management of the Gita Nada Marine Conservation Area by identifying all problems and solutions to achieve them. The method used in this study is a qualitative method. The type of data used is secondary data from literature studies, articles and websites of the NTB Fisheries and Marine Service, the West Lombok Regency Marine and Fisheries Service and the Central Statistics Agency (BPS). Data analysis was carried out using the Zieobjective Oriented Project Planning (ZOOP) Method, a project planning method that is oriented towards goals. Based on the results of the study, it can be concluded that the problems in the management of the Gita Nada Marine Conservation Area (MCA) are over-exploitation of fish resources, degradation of mangroves and coral reefs and limited funding sources for supervision and monitoring. The planning program carried out includes institutional bio-physical and socio-economic surveys, socialization and advocacy for the management of the Gita Nada MCA, preparation of regulations for community-based coastal and marine resource management, rehabilitation of coastal ecosystems, facilitation of facilities and infrastructure, empowerment of coastal communities, and periodic supervision and monitoring.